Travelling hair pains of the past: The continued impact of colonialism on the construction of black women's hair - Zulu, Buhle (Department of Political Studies, 2025)
The study of Black women's hair politics is recent. It refers to the existing social discussions and analyses of Black women's hair by Black women. And focuses on Black women's racial, gendered, political, and personal experiences with their hair. It explores how their views relate to dominant societal meanings attached to their hair. Over the years, this conversation has helped Black women voice and uncover how others perceive their hair. They explore these perceptions in the context of race, gender, location, and class. One dominant narrative that has emerged out of this discourse is the recurring issue of emotional pain experienced by Black women with African textured hair. From the early 1980s to the late 2000s, academic studies showed that Black women's pain about their African-textured hair came from historical racial discrimination and Euro-American beauty standards. Furthermore, these studies showed that western biases informed by discrimination target Black women and their hair. The dissertation analyzes the historical relationship between African and American experiences of Black women and Black hair. It explores how slavery connects these contexts. Furthermore, it examines three critical gaps in the association of Black women's African textured hair with pain. Firstly, the dissertation examines how African textured hair got to be associated with pain over the years. Secondly, it traces how racial historical perceptions on Blackness transformed the pain of having African textured hair to be solely centered on Black women. Thirdly, the dissertation explores how biological determinism during the American slavery era led to the perception of associating African textured hair with pain to be a Black female problem. This dissertation argues that the historical habitual tendency to associate Black women's African textured hair with pain, travels and is a repetitive issue that still affects Black women today. This dissertation used the postcolonial feminist research method. It included an in-depth discourse analysis of existing academic literature on Black women's hair discourses. It also analyzed the work of post-colonial (feminist) theorists in the areas of Black Feminist Thought and Transnational Feminism. This dissertation also analyzes contemporary material data from academic journals, newspaper articles, and YouTube material from the early 2000s Natural Hair Movement (NHM).